(untitled) (CIPEEX, 2025)
Anamnesis is a fundamental process in aesthetic clinical practice, crucial for identifying the needs and health conditions of patients. In aesthetic clinics, anamnesis goes beyond simple data collection, involving a deep understanding of the medical history, expectations, and specific conditions that can influence the results of the procedures. In aesthetic clinics, the anamnesis is usually carried out freely, with the aim of having a friendly conversation with the patient to get to know them better, understand their routine, habits, daily care, and expectations regarding the procedure performed. It is a moment of knowledge, allowing the professional to evaluate the best way to perform the procedure to achieve successful results. The objective of this review is to analyze the practice of anamnesis in aesthetic clinics, exploring its importance in the personalization of treatments. The review highlights the benefits of a complete and detailed anamnesis and how it contributes to the effectiveness and satisfaction of aesthetic procedures. The methodology involved a systematic review of scientific articles published between 2019 and 2024. Databases such as PubMed, Scopus, and Google Scholar were used, with search terms including "anamnesis in aesthetic clinics," "patient history in aesthetics," and "importance of anamnesis in aesthetics." The practice of anamnesis in aesthetic clinics is a process of great importance that needs to be well conducted. Carrying out a thorough collection of information contributes to the personalization of treatments, adjusting techniques and products to the specific needs of each patient. Anamnesis is fundamental for successful clinical practice. Through detailed and careful information collection, professionals can tailor treatments to individual patient conditions and expectations, ensuring greater safety and efficacy. Recent studies confirm that effective anamnesis prevents complications and improves satisfaction and outcomes in aesthetic procedures. Thus, strict implementation of anamnesis should be a priority for aesthetic clinics aiming to offer personalized and high-quality care.